Romney - Hind, C. Lewis (Charles Lewis), 1862-1927 (Salt Lake City, UT : Project Gutenberg, 2011)
"Romney" by C. Lewis Hind is a biography written in the early 20th century that provides an in-depth look at the life and career of the English painter George Romney. The book chronicles Romney's artistic journey, detailing his rise to prominence in the late 18th century and the vicissitudes he faced throughout his career. Focused on his contribution to portrait painting, it explores themes of love, success, artistic ambition, and the nuanced relationships he maintained, particularly with his wife and his muse, Emma Hamilton. The narrative delves into the key periods of Romney's life, from his modest beginnings in Kendal to becoming a sought-after portraitist in Cavendish Square, where he painted many notable figures of his time. Hind discusses his rivalry with contemporaries like Sir Joshua Reynolds, highlighting his artistic philosophy and struggles with self-doubt. Central to the biography is his complex relationship with Emma, which invigorated his work but also contributed to personal turmoil after her marriage to Sir William Hamilton. The book illustrates how, despite Romney's declining health and resulting isolation in his later years, his artistic legacy endures, marked by the timeless beauty present in his portraits. (This is an automatically generated summary.)
Release date is 2011-08-01
Produced by Al Haines
Keywords: Romney, George, 1734-1802